Increasing students' skills in Operations managemen classes: Cumbuca Method as teaching-learning strategy - Junior, Jorge Muniz [UNESP]; De Souza Rodrigues, José [UNESP]; Assis, Alice [UNESP]; De Paula Oliveira, Francisca Clara; Franco, Bruno Chaves [UNESP]; MaCiel, Fabricio Gomes [UNESP] (FapUNIFESP (SciELO), 2017)
This paper analyses the use of the Cumbuca Method as a teaching strategy to develop reading skills in engineering students. Despite their importance, reading skills are little stimulated in engineering undergraduate courses. Teamwork, communication, organization and exposure of ideas, time management are also important skills to new employees. The Cumbuca Method was created to disseminate quality concepts among company employees, by discussing text related to a given topic of interest. This analysis is based on a qualitative approach involving a sample of 200 engineering undergraduates from Operations Management discipline at a public University in the State of Sao Paulo, Brazil. The results showed that the use of this teaching strategy inducted improvements to regular reading and debate among students.
Keywords: Operations Management; Reading; Teaching strategy; Undergraduation